2021
DOI: 10.3390/nu13072204
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of A Whey-Protein and Galacto-Oligosaccharides Based Product on Parameters of Sleep Quality, Stress, and Gut Microbiota in Apparently Healthy Adults with Moderate Sleep Disturbances: A Randomized Controlled Cross-Over Study

Abstract: People experiencing sleep problems may benefit from nutrients supporting serotonin metabolism and stress reduction. We studied the effect of a dairy-based product (DP) containing protein, galacto-oligosaccharides, vitamins and minerals, on sleep quality, stress, and gut-microbiota. In a cross-over RCT (three weeks intervention; three weeks washout), adults (n = 70; 30–50 y) with sleep disturbances (Pittsburgh Sleep Quality Index (PSQI) ≥ 9) consumed products 1 h before bed-time. Sleep quality (PSQI) was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Nineteen eligible studies examined the influence of microbiota modulators on brain structures/function and/or aspects of cognition and/or markers of stress and emotional well-being (both biological and perceived/self-reported) were included [ 35 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Microbiota modulators ranged from a single-species, multi-species probiotic, prebiotic, paraprobiotic and/or postbiotic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen eligible studies examined the influence of microbiota modulators on brain structures/function and/or aspects of cognition and/or markers of stress and emotional well-being (both biological and perceived/self-reported) were included [ 35 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Microbiota modulators ranged from a single-species, multi-species probiotic, prebiotic, paraprobiotic and/or postbiotic.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies used a prebiotic intervention [ 35 , 44 , 54 , 56 ]. Two studies examined galacto-oligosaccharides [ 35 , 54 ], one study used oligofructose-enriched inulin [ 56 ] and one study used a polydextrose fibre (PDX) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, combinations of whey and eggs with inulin have been shown to increase the capability to improve the gut microbiota in obese rats [173]. A randomized trial reported that whey protein with GOS improved sleep quality and stress through modulation of the gut microbiota [174]. Lastly the effects of lifestyle effects relevant to prudent nutritional practices and the adoption of some form of exercise regimes provide practical solutions to improve the intestinal microbiome-host functionality and in turn also improve the lung-gut axis.…”
Section: Discussionmentioning
confidence: 99%
“…GOS intake reduced anxiety behavior, accompanied by physiologically reduced waking cortisol and fewer prominent rises and falls in cortisol. Sleep quality, stress, and gut microbiome were assessed in adults 30-50 years of age who consumed a dairy-based product with added GOS and vitamins and minerals over three weeks (1 h before bedtime) [95]. The test diet reduced salivary cortisol and stimulated beneficial bacteria.…”
Section: Preclinical Datamentioning
confidence: 99%